2002
DOI: 10.1016/s1350-4177(01)00108-0
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical bromination of acetophenones using p-toluenesulfonic acid–N-bromosuccinimide

Abstract: Substituted acetophenones react with N-bromosuccinimide (NBS) and p-toluenesulfonic acid (p-TsOH) in the presence of ultrasound in methanol at 35 +/- 2 degrees C to give alpha-bromoacetophenones in high yield. In the absence of ultrasound the reaction takes place at the boiling point of methanol (65 degrees C) and takes longer time. The reaction does not take place in the absence of p-TsOH thermally or sonically. However the reaction is possible under photochemical conditions in the absence of p-TsOH. The best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…In our process, it seems that NCS was not more efficient than DCDMH. Samant et al 24 suggested the mechanism of keto-enol tautomerism in the process of the bromination of substituted acetophenones using NBS and we thought the mechanism of our processes was possibly similar to the one that Samant et al mentioned.…”
Section: Resultssupporting
confidence: 62%
“…In our process, it seems that NCS was not more efficient than DCDMH. Samant et al 24 suggested the mechanism of keto-enol tautomerism in the process of the bromination of substituted acetophenones using NBS and we thought the mechanism of our processes was possibly similar to the one that Samant et al mentioned.…”
Section: Resultssupporting
confidence: 62%
“…Synthesis of 3-styrylcoumarins was performed following the scheme 1, which began with formation of the coumarin (2) by microwave assisted Pechmann reaction between resorcinol (1) and ethyl acetoacetate (Manhas et al, 2006). Compound (3), obtained by microwave assisted Williamson etherification reaction of coumarin (2) (Otero et al, 2014) in 85% yield, was brominated with NBS (Adhikari et al, 2002) to give the alkyloxybromocoumarin (4) in 75% yield. This compound was subjected to cross-coupling with various styrenes (5) under palladium catalysis (Heck reaction) (Sabrina et al, 2011), leading to the formation of seven 3-styrylcoumarins (6a-6g) in 35%-49% yields.…”
Section: Synthesis Of 3-styrylcoumarinsmentioning
confidence: 99%
“…On water, 4'-bromomethylacetophenone was the only product formed (Podgoršek et al 2009), whereas the treatment of 1a with NBS/SiCl 4 in MeCN furnished the compound 3a as the sole product (Salama and Novák 2011). Conversely, compound 1a was selectively α-brominated using NBS/PTSA under ultrasound irradiation in methanol (Adhikari and Samant, 2002). In contrast to the straight-chain functionalized derivatives, at the branched isopropyl 1c and cyclohexyl 1d acetophenones only α-bromination took place with no benzylic bromination observed (entries 4 and 5).…”
Section: Resultsmentioning
confidence: 99%